The Effectiveness of Cyber Notary Development Using Barcodes on Notarial Deeds in Indonesia - Farhana Yahya Abdullah; Noor Lailatul Izza; Aryani Witasari (JURNAL AKTA, 2024)
One of the problems that often occurs is the slow process of making notarial deeds which can hinder business and economic processes. This is caused by the large number of documents that must be signed and verified by the notary, as well as the signing process which is still done manually. Moreover, the use of digital information technology is increasingly penetrating various sectors, including in the process of making notarial deeds. However, the implementation of cyber notary in Indonesia still faces various challenges, especially related to effectiveness and security. Therefore, this study aims to develop cyber notary using barcodes on notarial deeds that can increase efficiency and security in making notarial deeds in Indonesia. The research method used is normative legal research with literature studies from secondary data where the data is obtained indirectly including primary legal materials. The results of the study show that the development of barcodes on notarial deeds can help increase the efficiency of the notarial deed making process by reducing the time and costs required. In addition, this model can also increase the security of data and information related to notarial deeds, thereby reducing the risk of manipulation or information leakage. The development of cyber notary, especially the use of barcodes on efficient and secure notarial deeds, is expected to make the notarial deed process in Indonesia more modern, transparent, and reliable. This research is expected to provide a positive contribution to the development of notarial technology in Indonesia and strengthen public trust in the legal process carried out in this digital era.